2021
DOI: 10.1111/ijcp.14764
|View full text |Cite
|
Sign up to set email alerts
|

Association of IGF‐1 and IGFBP‐3 levels with gastric cancer: A systematic review and meta‐analysis

Abstract: Purpose:Many studies have investigated the association between serum IGF-1 and IGFBP levels with gastric cancer (GC), but the results remained inconclusive. In this work, we performed a systematic review and meta-analysis to examine the precise association of serum levels of IGF-1 and IGFBP with GC.Methods:A comprehensive systematic search was carried out in PubMed/MEDLINE, SCOPUS, Web of Science, and EMBASE databases for (nested) case-control studies that reported the levels of IGF-1 and IGFBP in GC cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Many previous studies suggested that the alteration of IGFBP3 could affect many types of tumors including hepatocellular carcinoma [ 19 ], breast cancer [ 20 ], and lung cancer [ 21 ]. A study revealed that compared with healthy subjects, the level of serum IGFBP3 in patients with gastric cancer decreased significantly [ 22 ]. However, what the role of IGFBP3 is in EJA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies suggested that the alteration of IGFBP3 could affect many types of tumors including hepatocellular carcinoma [ 19 ], breast cancer [ 20 ], and lung cancer [ 21 ]. A study revealed that compared with healthy subjects, the level of serum IGFBP3 in patients with gastric cancer decreased significantly [ 22 ]. However, what the role of IGFBP3 is in EJA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that elevated serum IGF-1 levels are associated with an increased risk of multiple cancers. However, it has been observed that patients with gastric cancer have lower serum IGF-1 levels than healthy patients, which contradicts previously reported information about the IGF pathway [101]. It is a potent mitogen that has an antiapoptotic function and promotes the formation of cancer metastases [5].…”
Section: Igf-1 and Igf-2 As Carcinogens And Cancer-promoting Factorsmentioning
confidence: 87%
“…Overexpression of IGFBP-1 inhibits MMP-9-induced GC cell migration and protects against H. pylori-induced GC [80]. Although clinical studies have shown that IGFBP-3 can be used as a biomarker for the diagnosis and prognosis of esophageal gastric junction adenocarcinoma [81] and that the simultaneous decrease of IGFBP-3 and increase of IGF-I may promote tumor growth Journal of Diabetes Research [82], the mechanism underlying the relationship between these two potential biomarkers and GC has not been established. IGFBP-5 overexpression promotes the activity of the tumor suppressor factor PKNOX2, which can limit the development of GC [83].…”
Section: Effects Of Hyperglycemia and Hyperinsulinemia On Dm And Gcmentioning
confidence: 99%